Exploring knowledge translation mechanisms in the Western Cape Provincial Health System - Edwards Amanda (Health Policy and Systems Division, 2024)
The persistent gap between health research, policy and practice has led to a burgeoning interest in the field of knowledge translation (KT). However, there remains little clarity on what KT mechanisms work in different contexts, particularly in low and middle-income countries. Using mixed methodology this project explores KT mechanisms, barriers, facilitators and outcomes as they function in South Africa’s Western Cape provincial health system. Document review and key informant interviews with health system researchers and provincial health policymakers were synthesised with findings from a random sample of provincial study protocols registered on the National Health Research Database. An evidence-mapping of the literature on KT in African settings complemented this data. Findings indicate variations in the use of health-related research by provincial policymakers and diversity in the mechanisms employed for KT. The important role of organisations, characteristics of available research, relationships and networks play a facilitating role for KT in this context. Resource constraints, system conflicts and politics served as notable barriers. These findings have implications for health researchers and provincial policymakers seeking to “do” KT in the Western Cape health system – including the need for recognition of the important role of context, of the ethical dilemmas within KT processes, and the need for a more systematic approach to KT that includes embedded learning systems.